Funerary practices in the Netherlands - Mathijssen, Brenda; Venhorst, Claudia (Funerary international, 2019)
In contextualizing the Dutch funerary practice in its wider legal, national and local governance framework, this book describes the historical context for current practices, provides data on trends in burial and cremation, and examines recent developments including natural burial, increasing religious diversity and changing national legislation.Chapters provide an overview of funerary history and contemporary practice, alongside photographs, charts and tables of key information. Topics explored include: the death care industry; the Corpse Disposal Act; a typical funeral including funeral costs and insurance; cemetery and crematorium provision; and, the practices, technicalities and legalities of burial and cremation. The book also analyses and illustrates the commemorative practice of public mourning events related to World War II, the Holocaust and the MH17 plane crash.This book provides a broad frame of reference on funeral practices, making it a useful resource for academics, policy makers and practitioners interested in the historic, legal, technical and professional aspects of the funerary industry.